بيئات التعلم الإلكتروني وتغير أدوار المعلم - بومناخ, ياسر (University of El-oued, 2021)
يعد التعليم الإلكتروني أهم إستراتيجية طبقتها أغلب دول العالم في السنوات الأخيرة، في محاولة لجعل التعليم أيسر وأسهل على طرفي العملية التعليمية، وذلك دون إغفال مدى توفر التقنية وانتشارها خاصة عند المتعلم. ذلك أن التعليم الإلكتروني هو استعمال التقنية والوسائل التكنولوجية في التعليم وتسخيرها لتعلم الطالب ذاتيا وجماعيا وجعله محور المحاضرة، بدء بالتقنيات المستخدمة للعرض داخل الصف الدراسي من وسائط متعددة وأجهزة إلكترونية، وانتهاء بالخروج عن المكونات المادية للتعليم، بهدف نقل عملية التعليم من مجرد تلقين المعلم للمعلومات وتخزين المتعلم لها إلى العملية الحوارية التفاعلية بين الطرفين لتحسين مستوى التعليم، وذلك بمحاولة تشكيل ما أصبح يصطلح عليه بالصفوف الافتراضية التي تسمح بتفاعل أطراف العملية التعليمية عبر شبكات وتقنيات محددة. فما هي البيئات التعليمية التي تقوم عليها الوحدات التعليمية في التعليم الإلكتروني؟ وما هي أدوار المعلم فيها؟ Abstract: E-learning is rated the most important strategy implemented by most countries of the world in recent years, in an effort to make education easier on both sides of the educational process spectrum, without losing sight of the availability and spread of technology, especially amongst the learners.E-learning is the use of technology and technological means in education for the sake of empowering learners to self-learn and to learn collectively. It, likewise, pertains to making these tools the axis around which the lecture as such revolves. That includes, but not limited to, the techniques used for presentation in the classroom, such as multimedia andelectronic devices.It ends with a departure from the physical components of education, with the aim of moving the process of education from the mere teaching and storage information by the learner to the interactive dialogue process between the two parties to improve the level of education, by trying to shape what has become known as virtual classes that allow the interaction of the parties in the educational process through specific networks and techniques. The present research paper will attempt, therefore, to answer these two primary research questions, namely What are the various educational environments and educational modules in e-learning? What are the teacher's roles?
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: التعليم الإلكتروني _ التعلم الشبكي المباشر _ التعلم الشبكي المتمازج _ التعلم الشبكي المساند _ الوسائط المتعددة; E-learning - Direct Network Learning - Networking in Combination - Supportive Network Learning - Multimedia.